OPTIMIZING NAHWU LEARNING: COMBINATION OF ELECTRONIC AND CONVENTIONAL MIND MAPPING - Arifdo Putra; Mahyudin Ritonga; Hetti Waluati Triana (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2023)
This research discusses the results of action research aimed at enhancing the learning of Arabic Grammar through the combination of electronic and conventional mind mapping learning strategies. The problem addressed in this research is the low comprehension of students regarding Arabic Grammar material. Before the intervention, the student completion rate was only 55%, and their average score was low at 62. The research method employed in this study is action research, which involves a group of students in a continuous learning process over several cycles. The research results indicate that electronic and conventional mind mapping learning strategies significantly improved students' understanding of Arabic Grammar material. This improvement is evident in the completion rate, which increased to 81% in Cycle I and 90% in Cycle II. Students demonstrated an enhancement in their ability to identify and apply Arabic Grammar rules. Additionally, they displayed improvements in both oral and written communication skills in the Arabic language. Therefore, the combination of electronic and conventional mind mapping learning strategies can be an effective approach to enhance Arabic Grammar learning. The findings of this research offer valuable insights for educators seeking to improve the quality of Arabic Grammar.